Review of California sea lion (Zalophus californianus) abundance, and population dynamics in the Gulf of California. - Masper, Alice; Pablo Gallo-Reynoso-Reynoso, Juan; Ángel Cisneros-Mata, Miguel; García-Hernández, Jaqueline (Revista de Biología Tropical, 2019)
Introduction: The life history of the California sea lion (Zalophus californianus) in the Gulf of California is marked by a series of important events influencing and modifying its population growth, distribution, and evolution. Despite the fact that this population has been studied since the 1950s, research has been rather punctual and fragmentary. Before 2010, there are only a few surveys conducted simultaneously in all rookeries, thus there is no reliable information on key aspects of life cycle, population trend and potential threats. In the present work we conducted a review of California sea lion life history and environmental changes in the Gulf of California thorough a collation of survey data encompassing the last 37 years. Objective: Our aim was focused on identifying short- and long-term processes potentially acting on the population, and hopefully improve knowledge about the population trend and status using different points of view. Methods: We collected and analyzed population survey data from different sources since the 1970s to 2018: published papers, master's and doctoral thesis, in addition to technical reports. The survey data are organized in sections corresponding with crucial population life history events. Results: Considering a long-time period the population size appears to be stable with zero growth. Cyclic interannual fluctuation seem to denote a certain dependence with climatic factors, not directly with El Niño, but with sea surface temperature anomalies that determine prey availability. However, many doubts persist about the incidence of different local environmental factors on gender and age, particularly related with juvenile recruitment and female survival rate. Conclusions: In conclusion, more information is required based on seasonal surveys, life cycle, regional environmental variation. Statistical errors need to be assessed and monitoring methods should be standardized and must be considered to ascertain short- and long-term population and colony spatial-temporal patterns.